Critical nutrient ranges and evaluation of nutritional status in coffee-tree plantations of Minas Gerais - Martinez, Herminia Emilia Prieto; Menezes, June Faria Scherrer; Souza, Ronessa Bartolomeu de; Venegas, Víctor Hugo Alvarez; Guimarães, Paulo Tácito Gontijo (Pesquisa Agropecuaria Brasileira, 2003)
The objectives of this work were to define the critical nutrients ranges and evaluating the nutritional state of coffee-tree plantations with low, intermediate and high productivities in four areas of the State of Minas Gerais. Leaves of 312 sample units of 168 farms were collected in two consecutive years, one of high productivity and another of low productivity, according to the biennial cycle of the coffee-tree. In the leaves all the macronutrients and the micronutrients Cu, Fe, Zn, Mn and B were analyzed. With the results of the analyses the critical ranges of the nutrients in the years of low and high productivity and for each studied area were calculated, using as reference farms of high productivity (more than 1,800 kg/ha of green coffee in the average of two consecutive years). The diagnosis of the nutritional state of the farms in the studying areas was made through the frequencies of nutrients in deficient, appropriate and excessive levels. The obtained critical ranges did not differ either between the sampled years or among the areas. In the studied area nutritional problems with micronutrients were predominant.